Importance - Performance analysis of medical tourism in Tehran province from medical tourists and medical services providers\' perspective - B Delgoshaei; H Ravaghi; N Abolhassani (Tehran University of Medical Sciences, 2012)
Background: Developing countries request to alternative revenue resources. Iran as one of the developing countries with high potentiality for attracting medical tourist is seeking to enter medical tourism marketing .This study aimed to analyze the importance- performance of the Tehran as a capital city to medical tourism viewed by medical tourists and medical service providers. Materials and methods: This descriptive, cross-sectional study was carried out in Tehran selected hospitals in the 3th first months of 2011. The data were gathered by using a validated self-constructed questionnaire. The data were analyzed by descriptive statistical techniques. Results: The results indicate that the majority of the medical tourists are attracted from the United Arab Emirates (22.3%). The respondents considered medical tourism factors as an importance (M=4/40±0/61).The Tehran selected hospitals` performance is average as related to medical tourism factors (M=2/75±0/66). Conclusion: Despite the importance given to medical tourism factors by medical tourists and medical services providers, Tehran selected hospitals` performance is an average and there is no serious attempts are being made to attract medical tourists at macro levels. In spite the quality, variety and costs of the medical services and equipments in the selected hospitals are satisfactory, international accreditation of the hospitals are still in a major problems